Job-Seeking and Behavioral Preparedness of Graduating Students: A Career Guidance Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Newly graduated students experience challenges in searching for a job, and it is a challengethat should not be taken lightly. These challenges are often felt through rejection letters oremails sent by companies to applicants, even during uncomfortable interviews. Finding a jobcan be stressful, to say the least. It can be overwhelming to the point that newly graduatedpeople feel hopeless in seeking a job that suits their character, skills, and qualifications.The results showed that the highest age range is 19–22 years old, with 60%, and the lowest is27 and above, with 7.3%. In terms of course, BTVTED has 23%, and the lowest are BSCPEand BPED, which both have 3.6%. According to the results, problems encountered in terms oflack of experience have a weighted average of 2.36; lack of communication skills have aweighted average of 2.32; and lack of seminars and training have a weighted average of 2.29.The results for possible behavioral preparedness of graduating students to cope with jobseeking in terms of practicing interviews have a weighted average of 3.36, preparing acurriculum vitae or resume is 3.39, and seeking professional consultation has a weightedaverage of 2.25. The implication of this study is to propose a career guidance program to helpgraduate students succeed in their job-seeking process.The study shows that the problems encountered by graduating students are mostly a lack ofcommunication, which requires proper training for formal communication. The study showsthat the possible behavioral preparedness of graduating students is most likely practicinginterviews and preparing a curriculum vitae or resume. With that, the researchers will utilize acarefully crafted career guidance program for graduating students.
Keywords: Psychology